2009
DOI: 10.1039/b916017p
|View full text |Cite
|
Sign up to set email alerts
|

Study on selectivity of β-myrcene hydrogenation in high-pressure carbon dioxide catalysed by noble metal catalysts

Abstract: Hydrogenation of monoterpenes, such as b-myrcene, in high-density carbon dioxide over 0.5 wt.% Pd, or Rh, or Ru supported on alumina was investigated. Hydrogenation catalysed by Rh and Ru is generally faster in a single supercritical (sc) phase (gaseous reagents and solid catalyst) than in a biphasic system (liquid + gas reactants + solid catalyst). The reaction catalysed by Pd occurs faster in two phases. The final composition of the reaction mixture is strongly dependent on the noble metal catalyst used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Terpenes are obtained by fractional distillation of turpentine 1 and can be modified by catalytic methods 2 such as hydrogenation, [3][4][5] dehydrogenation, 6-14 rearrangement, [15][16][17] and oxidation reactions. Terpenes are obtained by fractional distillation of turpentine 1 and can be modified by catalytic methods 2 such as hydrogenation, [3][4][5] dehydrogenation, 6-14 rearrangement, [15][16][17] and oxidation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Terpenes are obtained by fractional distillation of turpentine 1 and can be modified by catalytic methods 2 such as hydrogenation, [3][4][5] dehydrogenation, 6-14 rearrangement, [15][16][17] and oxidation reactions. Terpenes are obtained by fractional distillation of turpentine 1 and can be modified by catalytic methods 2 such as hydrogenation, [3][4][5] dehydrogenation, 6-14 rearrangement, [15][16][17] and oxidation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide (CO 2 ) is an inert, inexpensive, easily available, odorless, tasteless, environment-friendly, and GRAS (Generally Recognized As Safe) solvent. The supercritical technology is a green sustainable process [6,7] in which the solvent power and selectivity can be tuned according to the operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Pd, the reaction performed in the supercritical phase was slightly slower than that under biphasic conditions. Pd/Al 2 O 3 was the most active catalyst and yielded the completely saturated product 2,6-dimethyloctane 80 [78]. The Rh/Al 2 O 3 catalyst led to monounsaturated 2,6-dimethyloct-2-ene 78 in only slightly smaller amounts than 2,6-dimethyloctane 80, whereas 2,6-dimethyloct-1-ene 79 was formed in minor quantities.…”
Section: Hydrogenation Of Myrcenementioning
confidence: 95%
“…Hydrogenation of b-myrcene 7 over Pd, Rh, and Ru supported on Al 2 O 3 in high-pressure CO 2 was carried out [78] (Scheme 23). A comparison of the reactions under biphasic conditions (118 atm) and in the supercritical phase (158 atm) demonstrated that the reactions over Rh and Ru catalysts performed in a single supercritical phase attained equilibrium faster than hydrogenation carried out in biphasic conditions.…”
Section: Hydrogenation Of Myrcenementioning
confidence: 99%